PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA - Desty Endrawati Subroto; Siti Nurhaliza; Sri Astuti (CV. Denasya Smart Publisher, 2025)
This study was conducted at SD Negeri Serang 11 with the aim of examining the relationship between the school environment and students' learning motivation. The school environment analyzed in this research includes two main aspects: the physical aspect, such as facilities and infrastructure, and the social aspect, such as relationships among students and interactions with teachers. Students' learning motivation is defined as both internal and external drives that encourage students to achieve academic success. This research employed a descriptive quantitative approach supported by a literature review from various credible sources. The findings revealed that a supportive school environment significantly impacts the improvement of students' learning motivation. Based on these findings, the study recommends efforts to enhance the quality of the learning environment to further strengthen students' motivation